The ritual practices of the naqshbandiyya-khalidiyya order in contemporary Malaysia - Syed Hadzrullathfi, Syed Omar; Mohd Shahril, Othman (2012)
This article will discuss the dhikr ism al-dhƗt, which is one of the ritual practices of the NaqshbandiyyaKhƗlidiyya Sufi order. The term ism al-dhƗt refers to the divine essence of God’s almighty name of ‘Allah.’ Using interviews and the observation-participant method, this qualitative study was conducted to evaluate whether the current practice of the Sufi order in the Malay Peninsula is coherent with the last prominent Naqshbandiyya scholars or not. The article attempts to highlight the modifications related to the practices that occur particularly in the KhƗlidiyya order in Malaysia. The study found that various manners of practice of the dhikr ism al-dhƗt in the Naqshbandiyya-KhƗlidiyya Sufi order applied in Malaysia nowadays are coincident with those of former Naqshbandi leaders who have engaged in such a variety of practices. The study showed not much difference or changes in implementation compared with the practices that took place in Malaysia at that time